Extracellular vesicle‐carried microRNA‐27b derived from mesenchymal stem cells accelerates cutaneous wound healing via E3 ubiquitin ligase ITCH. Issue 19 (26th August 2020) - Cheng, Shihuan; Xi, Zhiyu; Chen, Guang; Liu, Kai; Ma, Renshi; Zhou, Chen
Abstract: Mesenchymal stem cells (MSCs) have been highlighted as promising candidate cells in relation to cutaneous wound healing. The current study aimed to investigate whether MSC‐derived extracellular vesicles (EVs) could transfer microRNA‐27b (miR‐27b) to influence cutaneous wound healing. The miR‐27b expression was examined in the established cutaneous wound mouse model, and its correlation with the wound healing rate was evaluated by Pearson's correlation analysis. The identified human umbilical cord MSC‐derived EVs were co‐cultured with human immortal keratinocyte line HaCaT and human skin fibroblasts (HSFs). The mice with cutaneous wound received injections of MSC‐derived EVs. The effects of EVs or miR‐27b loaded on wound healing and cellular functions were analysed via gain‐ and loss‐of‐function approaches in the co‐culture system. Dual‐luciferase reporter gene assay was employed to verify the relationship between miR‐27b and Itchy E3 ubiquitin protein ligase (ITCH). Rescue experiments were conducted to investigate the underlying mechanisms associated with the ITCH/JUNB/inositol‐requiring enzyme 1α (IRE1α) axis. miR‐27b was down‐regulated in the mouse model, with its expression found to be positively correlated with the wound healing rate. Abundant miR‐27b was detected in the MSC‐derived EVs, while EV‐transferred miR‐27b improved cutaneous wound healing in mice and improved proliferation and migration of HaCaT cells and HSFs in vitro. As a target of miR‐27b, ITCH was found to repress cell proliferation and migration. ITCH enhanced the JUNB ubiquitination and degradation, ultimately inhibiting JUNB and IRE1α expressions and restraining wound healing. Collectively, MSC‐derived EVs transferring miR‐27b can promote cutaneous wound healing via ITCH/JUNB/IRE1α signalling, providing insight with clinical implications.